Freshwater fishes behavior in contact with Salmonella enteritidis var. danysz, La Habana, Cuba - Hernández, Natividad (1999)
The behavior of 13 species of fresh water fish from Cuba in contact with Salmonella enteritidis var danysz in a concentration 10 8 ufc/ml was evaluated for six months. In the evaluation use was made of alevines and juveniles from ponds in of the Guanímar and Manpostón stations located in Batabanó, Guanímar, Guajaibón and La Lisa (Havanna city). Before the assay began, the fishes were put to a 15 day period of adaptation to captivity During the assays, physico-chemical parameters of the water from the ponds were recorded, and 48 hours after inoculation an increase in the amount of nitrites and nitrates was found. Extreme length and weight measurements of the fish were recorded, and no significant differences were found compared to the control group. At the end of the experiment all the fishes presented a normal aspect, which shows that the dose of Salmonella enteritidis var danysz made use of was harmless to the fishes.